IMPACT DE LA FRACTURATION SUR L’ARCHITECTURE DU RESEAU HYDROGRAPHIQUE (CAS DE LA REGION DE SMAALA, MAROC CENTRAL HERCYNIEN) APPORT DU SIG ET DE LA TELEDETECTION - Oubbih, Jamal; El Mahdaouy, Aziz; El Mansouri, Bouabid; Mridekh, Abdelaziz; Chakiri, Said; Elbelrhiti, Hicham (European Scientific Journal, ESJ, 2015)
In the Smaala area, Paleozoic rocks crop out and are structured by the Hercynian orogeny. The hydrographic network is dense and displays various flow directions. It consists of temporary streams that eventually lead to the Grou river. Analysis of the Landsat TM satellite image can extract lineament network. The majority of these lineaments coincide with geological fractures identified on the field. Their distribution is organized around four major directions: NE-SW, N-S, NW-SE and E-W. The comparison of the statistics of the hydrographic network with those of lineaments shows that the majority of rivers are affected by geological structures, especially the fracturing. The topography of the area also has a secondary impact on the water circulation, by the presence of slopes generally oriented North-West and North.